Performance evaluation of solar assisted membrane distillation for seawater desalination using solar simulator - Mohd Amirul Hilmi, Mohd Hanoin; Nadzirah, Mohd Mokhtar (ISRES Publishing, 2022)
The increase in freshwater demand and environmental pollution is leading to an increase in the use of renewable energy for the seawater desalination system. The emerging potential in seawater desalination technology is a solar assisted membrane distillation (SAMD) where thermal energy is supplied from the solar thermal collector to the membrane module. The objective of this study is to evaluate the performance of in-house made SAMD system for seawater application in terms of the permeate flux and salt rejection using solar simulator. In this work, Flat Plate Solar Thermal Collector (FPSC) system was designed to preheat the simulated and actual seawater as the feed solution for indoor assessment. 2.5 wt.% of sodium chloride (NaCl) was used represents the standard seawater. The heat radiation intensity remained constant during the experiment by using the tungsten lamps which are widely used as a solar simulator. During simulated seawater testing, the initial permeate flux of 3.86 kg/h.m2 was obtained, then increased up to 5.39 kg/h.m2, with almost 39.4% increment. This shows a similar trend with seawater MD processes. Nonetheless, the flux slightly decreased until 4.06 kg/h.m2, showing about 24.7% flux reduction. Then, the flux remains decreased at a slower rate down to 3.90 kg/h.m2. The declining trend in permeate flux can be attributed to the low evaporation area affected by the NaCl crystallization due to the partial membrane pore blockage. Nevertheless, the membrane still obtained 99% salt rejection in all experiments.